Caught in a Productivity Trap: A Distributional Perspective on Gender Differences in Malawian Agriculture - Kilic, Talip; Palacios-Lopez, Amparo; Goldstein, Markus (World Bank, Washington, DC, 2013)
In targeting poverty gains, sub-Saharan African governments have emphasized the alleviation of gender differences in agricultural productivity. The empirical studies on the gender gap, however, have frequently used data that were limited regarding geographic and topical coverage, and/or details on intra-household dynamics. The study provides a nationally-representative analysis of the gender gap in Malawi, and decomposes it, for the first time, at the mean and at selected points of the agricultural productivity distribution into (i) a portion driven by gender differences in levels of observable attributes (the endowment effect), and (ii) a portion driven by gender differences in returns to the same set of observables (the structure effect). Sequentially, the authors unpack the relative contributions of different factors towards the gender gap, and suggest future research priorities to inform policy interventions. The authors find that while female-managed plots are, on average, 25 percent less productive, 82 percent of this differential is explained by differences in endowments, mainly due to high-value crop cultivation and levels of household adult male labor inputs. The factors driving the structure effect include child dependency ratio and effectiveness of household adult male labor and inorganic fertilizer. The gender gap increases across the productivity distribution, ranging from 22 percent at the 10th percentile to 37 percent at the 90th percentile. While it is explained predominantly by the endowment effect in the first half of the distribution, the contribution of the structure effect towards the gender gap increases steadily above the median, standing at 34 percent at the 90th percentile.